Petitioning by clerks and the colonial state in late nineteenth-century Burma. (3rd July 2021) - Iwaki, Takahiro
ABSTRACT: Many indigenous people in British Burma were employed as subordinate officials in governmental agencies. This article focuses on the Burmese clerks in the delta region, and explores the characteristics of their relationship with the colonial state in the late nineteenth century. First, the recruitment process and careers of specific clerks are overviewed. Their position was gradually institutionalized by appointment rules. However, population growth and the development of a rice-export economy entailed not only a surge of judicial and revenue work but also territorial changes in administrative units and rearrangements of staff. The workload of the delta's administration increased, placing additional burdens on clerks. By examining the case of a clerk who experienced dismissal and reinstatement, the article reveals that high-ranking officials, under the pedagogical functions of the colonial state, adopted a stance of restricting dismissals. Moreover, regarding the significance of petitions produced and submitted by clerks, each clerk, as a petitioner, appeared to have a distinct strategy, since not every document is stereotypical in its form or phraseology. In other words, petitioning, in this study, is not treated as a one-sided supplication but rather as an interaction between petitioners and recipients.